New Cosmopolitanisms, Race, and Ethnicity Cultural Perspectives. Ed. by Ewa Barbara Luczak, Anna Pochmara, Samir Dayal - Grazia Micheli (Iperstoria, 2020)
Review by New Cosmopolitanisms, Race, and Ethnicity Cultural Perspectives. Edited by Ewa Barbara Luczak, Anna Pochmara, Samir Dayal